2023
DOI: 10.1007/s10055-023-00775-2
|View full text |Cite
|
Sign up to set email alerts
|

Suitability test of virtual reality applications for older people considering the spatial orientation ability

Abstract: Previous studies showed similar spatial orientation ability (SO) between real world (RW) and virtual reality (VR). As the SO deteriorates with age, it is crucial to investigate whether the degradation is similar in VR, as it may affect the use of VR tools for older people, such as in physical therapy. Therefore, we extended our previous study, in which similar SO between RW and VR was measured for younger participants (18–35 years) with a higher age group (> 55 years) to examine the VR's influence on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Cybersickness was measured by the Simulator Sickness Questionnaire (SSQ) ( 12 ). This questionnaire has been previously used in several studies to assess cybersickness ( 27 , 28 ). The French-Canadian translation ( 29 ) of this questionnaire, measuring VR’s side effects among a sample of French-speaking participants, was used.…”
Section: Methodsmentioning
confidence: 99%
“…Cybersickness was measured by the Simulator Sickness Questionnaire (SSQ) ( 12 ). This questionnaire has been previously used in several studies to assess cybersickness ( 27 , 28 ). The French-Canadian translation ( 29 ) of this questionnaire, measuring VR’s side effects among a sample of French-speaking participants, was used.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a pilot study exploring age differences in presence found that older adults preferred a slower pace and more explicit instructions in VR [35]. Another study shows that older adults may have reduced visual acuity and hearing, which can affect their ability to interact with VR environments [36]. VR developers can consider the familiarity of different age groups with technology and adjust the level of complexity of VR experiences accordingly.…”
Section: Factors Affecting User Experience In Virtual Environmentsmentioning
confidence: 99%
“…Overall, the study highlights the potential benefits of using VR technology in aged care, as well as the need for design improvements to ensure its effective use with older adults. Other studies have focused on spatial orientation, such as [8], in which the authors investigate whether the decline in spatial orientation with age is similar in virtual reality (VR) as it is in the real world; such studies are important, as they could influence the efficacy of VR tools for older people, particularly in physical therapy. The study showed a similar influence of VR on the spatial orientation of both age groups, supporting the usage of VR regardless of age.…”
Section: Vr Environments For Eldersmentioning
confidence: 99%
“…Thanks to these attributes, modern virtual environments, initially used only for gaming purposes, are now being exploited for a variety of tasks, such as sports activities, simulation, or even surgical techniques [2]. Moreover, VR is being used for rehabilitation, modernising the clinical approach for people with various diseases and conditions, such as for those undergoing rehabilitation after a stroke [3][4][5] or with cerebral palsy [6], or for other reasons such as physiotherapy [7] or orientation [8]. These health applications of VR have gained attention in recent years because conventional exercise methods in rehabilitation facilities are time-and space-consuming and expensive, as they need effort from human health professionals [9].…”
Section: Introductionmentioning
confidence: 99%